2019
DOI: 10.1080/1359432x.2019.1634549
|View full text |Cite
|
Sign up to set email alerts
|

Collateral damage associated with performance-based pay: the role of stress appraisals

Abstract: Drawing on stress appraisal and self-determination theories, we hypothesized that the more requirements of performance-based pay are appraised as a challenge, the more individuals will feel less strain and be more prosocial, and that these effects will be explained by autonomous motivations. Conversely, the more requirements of performance-based pay are appraised as a hindrance, the more individuals will feel more strain and be less prosocial, and these effects will be explained by controlled motivations. An e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 85 publications
1
24
0
Order By: Relevance
“…Second, we confirm studies of the health-related outcomes of pay-for-performance plans (e.g., Dahl and Pierce 2020;Davis 2016;Parker et al 2019) in the specific context of sales and salespeople (Ganster et al 2011). This confirmation is important, because researchers have questioned whether the influence of pay-for-performance plans on health are sufficiently important to be studied at all (Pfeffer 2019).…”
Section: Theoretical Implications and Further Researchsupporting
confidence: 76%
See 1 more Smart Citation
“…Second, we confirm studies of the health-related outcomes of pay-for-performance plans (e.g., Dahl and Pierce 2020;Davis 2016;Parker et al 2019) in the specific context of sales and salespeople (Ganster et al 2011). This confirmation is important, because researchers have questioned whether the influence of pay-for-performance plans on health are sufficiently important to be studied at all (Pfeffer 2019).…”
Section: Theoretical Implications and Further Researchsupporting
confidence: 76%
“…Second, the nature of the relationship between variable pay and health remains unclear in several respects. To begin, only one field study provides causal evidence from the field (Timio, Gentili, and Pede 1979), while the remaining studies offer either correlational evidence (Dahl and Pierce 2020;Davis 2016) or evidence from the lab (Parker et al 2019). Further, most studies ignore important contingencies that might influence this relationship (the study by Dahl and Pierce [2020] is an exception).…”
mentioning
confidence: 99%
“…When the participants were questioned on whether they had other options that could lead to better results in their performances, 90% of them gave an affirmative No, while the 10% were undecided. According to Parker et al (2018), based on stress appraisal and self-determination theories, performance-based pay systems works favorably for individuals because they tend to feel less strained and more prosocial, leading to autonomous motivations. In other words, the recognition of individual effort is essential in encouraging the employees to improve their performance.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, found that workload, responsibility, role ambiguity, and role conflict could simultaneously be appraised as challenges and hindrances (for similar findings see Prem, Ohly, Kubicek, & Korunka, 2017;. Goal difficulty (Espedido & Searle, 2018) and performance-based pay (Parker et al, 2019) can be appraised as challenges and threats. Specifically, the results showed that on average, work stressors are positively related to challenge appraisals (k = 34, r = .151), hindrance appraisals (k = 19, r = .238), and threat appraisals (k = 9, r = .247).…”
Section: Resultsmentioning
confidence: 88%
“…studies employed an experience-sampling design or diary design (e.g., Ma Peng et al, 2021;, and 2 used experimental designs (1 field experiment, van Steenbergen, Ellemers, Haslam, & Urlings, 2008; 1 scenario experiment, Parker, Bell, Gagné, Carey, & Hilpert, 2019). Our review also found that 13/70 studies used multi-source measurement (e.g., Fugate, Prussia, & Kinicki, 2012;.…”
Section: Methodsmentioning
confidence: 82%